2009
DOI: 10.1111/j.1467-8535.2009.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Paging and scrolling: Cognitive styles in learning from hypermedia

Abstract: This study investigates the navigational patterns and learning achievement of university students with different cognitive styles, on hypermedia learning environments using paging or scrolling. The global-local subscales of Sternberg's Thinking Styles Inventory, two hypermedia, one using paging, the other using scrolling, a multiple choice achievement test, and a questionnaire to collect the students' satisfaction on paging/scrolling were used as data collection tools. This study finds that the cognitive style… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…Conversely, Baker (2003) confirmed that participants using Paging took significantly longer to read passages than those using Scrolling, and that reading comprehension with both text display types did not differ significantly. Eyuboglu and Orhan (2011) demonstrated that the cognitive style and Paging/ Scrolling, together or separately, did not affect learning or the satisfaction of learners. Further, students with different cognitive styles using Paging or Scrolling did all learn well, and their learning performance did not differ significantly.…”
Section: Introductionmentioning
confidence: 96%
“…Conversely, Baker (2003) confirmed that participants using Paging took significantly longer to read passages than those using Scrolling, and that reading comprehension with both text display types did not differ significantly. Eyuboglu and Orhan (2011) demonstrated that the cognitive style and Paging/ Scrolling, together or separately, did not affect learning or the satisfaction of learners. Further, students with different cognitive styles using Paging or Scrolling did all learn well, and their learning performance did not differ significantly.…”
Section: Introductionmentioning
confidence: 96%
“…El seguimiento es abordado utilizando agentes computacionales, cuya función es hacer el rastreo respecto a la ruta escogida, además sirven de ayuda a los usuarios en cuanto al suministro de información alusiva al contexto dado. Por tanto se define la variable de entrada difusa X= "Ruta" : [1,5], con tres conjuntos difusos "difusa", "alterna", "óptima".…”
Section: Diseño De Sdeaunclassified
“…Incursionando en los ambientes de formación mediados por tecnología web, se han hecho una serie de estudios como el llevado a cabo por [5] para determinar si existe una relación entre los patrones de navegación (paginación y desplazamiento) de los estudiantes en un sistema de formación basado en la hipermedia y los logros de aprendizaje. En este caso se adoptó el inventario de estilos de aprendizaje de [6] se conformaron dos grupos de seguimiento, un grupo usaba paginación como elemento de navegación y el otro utilizaba desplazamiento.…”
Section: Introductionunclassified
“…Some researchers have identified issues with inconsistencies around desktop web-based interaction versus mobile web-based interaction which make transitioning across these devices more difficult (Keinänen, 2011 andShrestha, 2007). Recent work on paging versus scrolling on the desktop (Baker, 2003, Bernard, Baker and Fernandez, 2003, Eyuboglu and Orhan, 2011, Grace, 2005, Kim and Albers, 2001, Peytchev, Coupe, McCabe and Crawford, 2006and Santosa, 2011 suggests that no statistically significant difference exists between the two interaction techniques for within document searching. The work of Santosa (2010) found that differences do exist for 'textbook' style interaction (less preferred).…”
Section: Introductionmentioning
confidence: 99%
“…The work of Santosa (2010) found that differences do exist for 'textbook' style interaction (less preferred). Eyuboglu and Orhan (2011) investigated the impact of cognitive style combined with paging or scrolling on achievement and satisfaction and found no statistically significant differences. Sanchez and Wiley (2009) found that paging had a positive effect on cognitive ability (and conversely, scrolling can have a negative one) under certain conditions for lower working memory capacity readers.…”
Section: Introductionmentioning
confidence: 99%